HEALTHCARE PROVIDER PATIENT NONVERBAL COMMUNICATIVE BEHAVIOUR ON DIABETES MELLITUS MANAGEMENT PRACTICES IN SELECTED HOSPITALS IN KENYA - Ungaya, Geoffrey; Mberia, Hellen; Wa Ngula, Kyalo; Sigilai, William; Sokwalla, Saira (International Journal of Communication and Public Relation, 2021)
Purpose: To examine the effect of healthcare provider patient communication nonverbal communicative behaviour on diabetes mellitus management practices in selected hospital in Kenya. Methodology: This was a causal comparative research design study with application of quantitative methodology. The study was carried out at Kenyatta National Hospital (KNH) and MP Shah Hospital. Systematic random sampling was used to sample patients. 400 participants were involved in the study and comprised 313 patients at KNH and 87 patients at MP Shah Hospital studied between the months of February 2019 and November 2019. The researcher administered questionnaire was used to collect data. The results were summarized using percentages and means or medians for categorical and continuous data respectively. Comparisons were done using chi square test of association of categorical variables and independent t-test for comparison of means. Linear regression and ANOVA were used to test for associations and hypothesis between healthcare provider patient nonverbal communicative behaviour (NVCB) and diabetes mellitus management practices (DMMPs). Findings: The rating of nonverbal communicative behavior was significantly higher at MP Shah Hospital than at KNH, p=0.010. Nonverbal communicative behavior had positive significant effect on diabetes mellitus management practices in Kenya [Î²=0.15, (95% CI 0.03, 0.27), p=0.016] with similar outcome at KNH [Î²=0.20, (95% CI 0.08, 0.33), p=0.002] and not at MP Shah Hospital [Î²=0.03, (95% CI 0.37, 0.42), p=0.899]. Thus, the null hypothesis was rejected in Kenya; the null hypothesis was rejected at KNH; the null hypothesis was not rejected at MP Shah Hospital. Therefore, there was significant effect of NVCB on DMMPs in Kenya, at KNH and not at MP Shah Hospital. Unique contribution to theory, practice and policy: Nonverbal communicative behaviour was responsible for improved performance in diabetes mellitus management practices among patients in Kenya and at KNH. At MP Shah Hospital, NVCB was not responsible for improvement in the DMMPs. The findings reinforce uncertainty reduction and communication accommodation theories basis in the dyadic interaction between patients and healthcare providers. Therefore, NVCB needs to be well conceptualized and incorporated at the health ministry and medical training institutions to equip medical workers with the required communication skills.